2015
DOI: 10.1007/s10637-015-0310-y
|View full text |Cite
|
Sign up to set email alerts
|

LY2603618, a selective CHK1 inhibitor, enhances the anti-tumor effect of gemcitabine in xenograft tumor models

Abstract: Pharmacological inhibition of CHK1 in the absence of p53 functionality leads to abrogation of the S and G2/M DNA damage checkpoints. We report the preclinical therapeutic activity of LY2603618 (CHK1 inhibitor) at inhibiting CHK1 activation by gemcitabine and enhancing in vivo efficacy. The in vivo biochemical effects of CHK1 inhibition in the absence or presence of DNA damage were measured in human tumor xenograft models. Colon, lung and pancreatic xenografts models were treated with gemcitabine, LY2603618, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Thus interference with DNA damage checkpoints by CHK1 inhibition has been demonstrated to be an effective means of increasing the cytotoxicity of gemcitabine. As expected, we observed synergistic anti-pancreatic cancer activities of LY2603618 and gemcitabine in 5 pancreatic cancer cell lines with different p53 phenotype, consistent with several preclinical studies (24)(25)(26), suggesting that p53 status does not play a major role in sensitization of gemcitabine by LY2603618. Moreover, the combination induced pronounced levels of apoptosis as indicated by an increase in the fraction of sub-G1 cells or in the levels of cleaved PARP and caspase-3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus interference with DNA damage checkpoints by CHK1 inhibition has been demonstrated to be an effective means of increasing the cytotoxicity of gemcitabine. As expected, we observed synergistic anti-pancreatic cancer activities of LY2603618 and gemcitabine in 5 pancreatic cancer cell lines with different p53 phenotype, consistent with several preclinical studies (24)(25)(26), suggesting that p53 status does not play a major role in sensitization of gemcitabine by LY2603618. Moreover, the combination induced pronounced levels of apoptosis as indicated by an increase in the fraction of sub-G1 cells or in the levels of cleaved PARP and caspase-3.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the combination induced pronounced levels of apoptosis as indicated by an increase in the fraction of sub-G1 cells or in the levels of cleaved PARP and caspase-3. Mechanistic investigations showed that CHK1 inhibition by LY2603618 partially abrogated S and G2/M phase checkpoints and significantly enhanced DNA damage in gemcitabine-treated pancreatic cancer cells, which is consistent with an in vivo study (26). This suggests that the abrogation of S or G2/M checkpoint contributes to sensitization of gemcitabine by LY2603618.…”
Section: Discussionsupporting
confidence: 86%
“…Inhibition of CHK1 function, using either small molecule inhibitors or siRNA, is known to be synergistic with gemcitabine and other drugs that cause DNA replication stress [ 62 67 ]. Based on the increased level of replication stress in Ewing sarcoma cells and the known sensitivity of Ewing sarcoma cells to ATR inhibitors, we tested a CHK1 inhibitor (LY2603618) as a single agent to evaluate the effect of inhibition of CHK1 on the viability of Ewing sarcoma cells [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the increased level of replication stress in Ewing sarcoma cells and the known sensitivity of Ewing sarcoma cells to ATR inhibitors, we tested a CHK1 inhibitor (LY2603618) as a single agent to evaluate the effect of inhibition of CHK1 on the viability of Ewing sarcoma cells [ 25 ]. In a dose-response assay, Ewing sarcoma were sensitive to treatment with LY2603618, a potent inhibitor of CHK1, for 6 hours (Figure 4A ) and 72 hours ( Supplementary Figure 6 ) with IC50 values of ~2 μM and ~500 nM, respectively [ 62 , 68 70 ]. To determine the concentration of LY2603618 required to inhibit CHK1 function we treated Ewing sarcoma cells with gemcitabine in combination with different concentrations of LY2603618 and then assessed CHK1 activation using immunoblotting for CHK1-Ser296, which is an auto-phosphorylation site in the CHK1 protein [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been expected that GEM treatment and Chk1 inhibition are likely to increase cell death owing to lethal chromosomal instability caused by cell cycle progression without repairing damaged DNA at the arrested S phase, this combined effect has been examined. As expected, this combined treatment inhibits colony formation (4), increases clonogenic cell death (6) and inhibits tumor growth compared with GEM treatment alone (7)(8)(9)(10). Phase I clinical trials have been initiated, and the recommended phase II dose has been shown (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 76%